Rheumatologists and Ophthalmologists Differ in Treatment Decisions for Ocular Behçet Disease. Issue 6 (September 2016) - Palestine, Alan Gary; Kolfenbach, Jason Roy; Ozzello, Daniel J.
Abstract : Background: Ocular involvement in patients with Behçet disease represents a significant clinical morbidity in this disease, and the prevention of visual impairment is an important treatment goal. There are no randomized controlled trials for the treatment of ocular Behçet disease; however, clinicians must still make treatment decisions. Objectives: The goals of this study were to describe the treatment preferences of rheumatologists and ophthalmologists for the treatment of ocular Behçet disease and to identify factors that influence these decisions. Methods: Eight hundred fifty-two rheumatologists and 934 ophthalmologists were surveyed via e-mail regarding their choice of therapy for a hypothetical patient with ocular Behçet disease. Respondents were asked to select first- and second-choice therapies and then reselect first and second choices assuming there would be no issues with cost or insurance prior authorization. Results: One hundred thirty two physicians (7.4%) who were willing to recommend treatment completed the survey: 68 rheumatologists and 64 ophthalmologists. The most common first-choice therapy for both specialties was a biologic agent. Significantly more rheumatologists than ophthalmologists chose methotrexate ( P < 0.025) and azathioprine ( P < 0.005) as their first-choice therapy. After assuming there were no concerns with cost or prior authorization, rheumatologists were still more likely to choose azathioprine compared with ophthalmologists ( P < 0.02), and ophthalmologists were more likely to choose local steroid implants ( P < 0.02). Both rheumatologists and ophthalmologists increased their choice of an anti–tumor necrosis factor agent when cost and prior authorization issues were removed ( P < 0.0001 and 0.008, respectively). Conclusions: Physician decision making is influenced by medical specialty and concerns regarding cost and prior authorization.